ANALISIS KINERJA KEUANGAN PADA PT SUMBER ALFARIA TRIJAYA TBK BERDASARKAN RASIO PROFITABILITAS DAN LIKUIDITAS PERIODE 2014-2023 - Fitriani, Cindy Herlina; Safii, Mohamad (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the financial performance of PT Sumber Alfaria Trijaya Tbk (Alfamart) during the period 2014–2023 using indicators such as Return on Assets (ROA), Return on Equity (ROE), Current Ratio (CR), and Quick Ratio (QR). The analysis is conducted to assess the company’s profitability and liquidity levels by comparing financial statements from previous years with industry standards. The research method used is descriptive quantitative, utilizing secondary data in the form of the company’s annual financial statements. The population in this study consists of PT Sumber Alfaria Trijaya Tbk’s financial reports from 2014 to 2023, while the sample includes the balance sheets and income statements for the years 2014 through 2023. The results of this study indicate that the financial performance of PT. Sumber Alfaria Trijaya Tbk during the period 2014–2023, measured through several financial ratios, is categorized as Less Healthy. The Return on Assets (ROA) shows an average value of 5.13%, which is below the Industry Standard of 30%. The Return on Equity (ROE) records an average of 15.96%, also below the Industry Standard of 40%. The Current Ratio (CR) averages 97.26%, far below the Industry Standard of 200%, while the Quick Ratio (QR) averages 40.85%, which is also below the Industry Standard of 150%. These findings indicate that the company’s financial performance in terms of profitability and liquidity is considered Less Healthy, according to the Industry Standards proposed by Kasmir as referenced in academic journals.